2019
DOI: 10.4414/smw.2019.20135
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of antimicrobial prescribing in a Swiss tertiary care hospital: a repeated point prevalence survey

Abstract: AIMS OF THE STUDY: Inappropriate use of antimicrobials is associated with the emergence of antimicrobial resistance and adverse events. Antimicrobial stewardship programmes may both optimise treatment of infections and reduce antimicrobial resistance but are implemented in only a minority of Swiss hospitals. In addition, data on prescribing patterns and quality are scarce. We conducted a repeated point prevalence survey to evaluate the quality of antimicrobial prescribing in a single tertiary care centre. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
0
27
2
Order By: Relevance
“…Antimicrobials are commonly used in the acute care setting. Recent studies found that approximately 30% of patients received antimicrobials during hospitalization [ 1 , 2 ], and 33% of antimicrobial prescriptions were considered inappropriate [ 3 ]. A multicenter study in Japan revealed an inappropriate antimicrobial use rate of approximately 40% for the inpatient population at acute care hospitals [ 4 ].…”
mentioning
confidence: 99%
“…Antimicrobials are commonly used in the acute care setting. Recent studies found that approximately 30% of patients received antimicrobials during hospitalization [ 1 , 2 ], and 33% of antimicrobial prescriptions were considered inappropriate [ 3 ]. A multicenter study in Japan revealed an inappropriate antimicrobial use rate of approximately 40% for the inpatient population at acute care hospitals [ 4 ].…”
mentioning
confidence: 99%
“…As well, Muhammed et al stated that about half (49.3%) of noncompliance to the guidelines in their study was found from surgical and gynecologic/obstetrics wards due to either longer duration of therapy or wrong timing ceftriaxone use in surgical prophylaxis [66]. Gürtler et al stated that 19.9% of all prophylactic prescriptions in a Swiss tertiary care hospital violated one or more appropriateness criteria, of which 40% concerned with extended postoperative surgical prophylaxis [67]. Komagamine et al stated that more than twothirds of the antimicrobial drugs used for surgical prophylaxis were administered for durations longer than 1 day, whereas the duration of antimicrobial drugs for surgical prophylaxis of 1 day or less has been found to be sufficient in most cases [68].…”
Section: Inappropriate Durationmentioning
confidence: 94%
“…A multivariate logistic regression model was performed to adjust the effects of potential factors that were significant in simple logistic regression ( p < 0.05). The selection of variables was based on biological plausibility and demonstrated association in other previous literature [ 39 ]. The percentage of agreement and Kappa coefficient were used to investigate an agreement between pathogen-directed therapy prescribed and AST results.…”
Section: Methodsmentioning
confidence: 99%